PENGEMBANGAN BAHAN AJAR KOMIK UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI EKOSISTEM HARMONIS SISWA KELAS V SDK ST. YOSEPH 4 KOTA KUPANG - Letik, Dewi Candra Grasia; Nitte, Yulsy Marselina; Ati, Chintia Marini Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in the subject of IPAS Harmonious Ecosystem material and the limited use of interesting and contextual teaching materials in the learning process. The purpose of this research is to develop teaching materials in the form of comics that are feasible, practical, and effective in improving the learning outcomes of social studies students in grade V of SDK St. Joseph 4 Kupang City. This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of grade V students as well as validators of material experts, media experts, and classroom teachers. Data collection techniques are carried out through observation, questionnaires, interviews, and learning outcome tests. Data were analyzed descriptively, quantitatively, and qualitatively. The results of the study show that the comic teaching materials developed obtained a very feasible category based on the results of validation of material experts and media experts. In addition, the results of the trial show that comic teaching materials are practically used in learning and are able to improve student learning outcomes in the Harmonious Ecosystem material. Thus, the comic teaching materials developed can be used as an alternative, interesting, interactive, and effective learning media to support IPAS learning in elementary schools.